Radio propagation prediction for selected locations in Sun-U campus: a ray tracing approach using image method - Lim, Soo Yong * (2011)
Radio propagation prediction is a crucial step to determine the propagation characteristics of any arbitrary installation for the implementation of a mobile radio system. This is especially true for telecommunication systems that use electromagnetic waves for information transfer instead of relying on the conventional way that use electrical currents. In this paper, a ray tracing approach using image method is adopted to perform radio propagation predictions in two selected areas of Sun-U Campus, namely an empty hallway located on the second floor in the School of Computer Technology (SCT), and its adjacent academic staff rooms. The values of electrical parameter such as dielectric constant (relative permittivity) of different materials are altered assuming the walls that separate each academic staff room are made of rubber, glass, and plasterboard. How this variation affects radio wave propagation prediction is discussed while the main propagation mechanisms traveling along the empty hallway are reported.